ALOKASI SAVING PENGELOLA TAMBAK YANG MELAKUKAN PEMBELIAN MELALUI PURCHASING CONSORTIUM - Nur Rahmawati; Ika Widya Ardhyani; Sinta Dewi (Journal of Research and Technology, 2018)
Purchasing Consortium (PC) is a strategy in purchasing wich two or more organizations with separate legal entities are merged either individually or through third parties. The main problem that arises in a PC is how to allocate the savings obtained to each member. Generally, the contributions given by each buyer in the purchase differ from one another. Allocation of savings equally to each buyer is no longer representing the contribution of each buyer.The purpose of this study is allocated savings using the Shapley value method of the cooperative game theory. Where each buyer obtained a saving allocation that is in accordancewith his contribution.Based on the results of the Shapley value, the results of saving allocations were matched with the contributions of each member who joined the PC. Where buyers 1 with a larger contribution get a greater contribution than the others. Keywords: Purchasing consortium, Shapley value